المراقبة الإلكترونية لقلب الجنين في أثناء المخاض - يوسف, أحمد; مرعي, رئيفة; سلطان, حنان (Latakia University Journal -Medical Sciences Series, 2019)
تضمنت الدراسة 150 ماخضاً , و تم تقييم حالة الجنين باستخدام : 1- أبغار الوليد في الدقيقة الأولى و الدقيقة الخامسة. 2- تخطيط قلب الجنين أثناء المخاض . 3- معايرة غازات الدم عند الوليد ( PH , PCO2 , PO2 , BE). و كانت النتائج كالتالي : 1- وجود علاقة عكسية هامة بين : أ‌- مشعر اليقظة / النوم و علامة أبغار . ب‌- ب - مشعر اليقظة / النوم و غازات الدم . 2- إن مشعر النوم / اليقظة المعكوس ≥ 2, التباطؤات من نمط DIP II , DIPIII اللانموذجية , وغياب الترددية ( حيث الشدة و التكرارية أقل من 3 ) تنبأت بتألم الجنين . 3- إن مشعر اليقظة / النوم ≥ 2 ,التباطؤات DIP III , و الترددية المتوسطة ( حيث الشدة والتكرارية بين 3-5 ) كانت علامات غير مطمئنة لحالة الجنين . In this study, 150 parturients have been included. Fetal state has been evaluated by the following methods: 1-Apgar score at 1th and 5th minutes; 2-Intrapartum fetal heart rate monitoring; 3- Neonatal blood gas parameters ( PH, PCO2, PO2, BE). The results were as following: 1.An important adverse relation exists between: Wake\sleep index and Apgar score Wake\sleep index and blood gas parameters. 2.Appearance of reverse sleep\wake index ≥2, DIPII, atypical DIPIII, and silent variability (where amplitude and frequency less than 3) were predictable of fetal distress. 3.Appearance of wake\sleep index ≥2, DIPIII, and median variability (where amplitude and frequency between 3-5) were warning signals of fetal distress.